Improvement of Science Process Skills Through Sound Variable Intensity Level Tool Kit - Royhanun Athiyyah; Taufiq Al Farizi; Dwi Nanto (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
Science process skills (SPS) are essential to assist the learning of senior high school students according to the 2013 curriculum, which prioritizes a scientific approach. The learning method that supports SPS is experiment methods. Nevertheless, learning with experimental methods is still rarely applied in schools, especially in the sound intensity level concept. The reason is the limited number and variant of experiment tool kits to support learning in schools. This study aims to develop a sound variable intensity level sound tool kit based on development procedures proposed by Jan van de Akker (2006). Sound variable intensity level kit was developed based on tool kit, which was developed before by Fikri Habibi. Sound variable intensity level experiment kit was evaluated by several learning media and learning material experts before being tested on high school students in several stages, including the one-on-one evaluation stages, small group evaluations, and field tests. The researcher revised the sound variable intensity level kit based on suggestions from the experts and the students. After being revised, the sound variable intensity level kit was tested on summative evaluation. Based on the results of summative evaluations, the sound variable intensity level kit becomes a successful, practical, and effective learning support tool kit for improving the science process skills of the student in the concept of sound intensity level.